ANALISIS PERSEPSI KONSUMEN TERHADAP BERAS ORGANIK DI PASABARU (FRESH MARKET) PADANG - Devi Analia; Evi Lutfiana Sa'diah; Ifdal Ifdal (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
This study aims to determine consumer perceptions of organic rice in Pasarbaru (Fresh Market) Padang City. Based on the results and discussion of the characteristics and consumer perceptions of organic rice in Pasabaru (Fresh Market), it is known that the importance performance analysis (IPA) explains the attributes that are considered important but whose performance is still low are rice taste and rice packaging. Attributes that are considered important and have good performance are rice cleanliness, rice free from the use of pesticides, service at sales points, availability of rice and promotions through social media. Attributes that were considered less important and whose performance was also considered normal by consumers were the color of the rice and prices that were competitive with other places. Attributes that consumers consider not too important but whose performance is considered good by consumers are the aroma of rice, the nutritional content of rice, environmental friendliness, price compatibility with benefits, easily accessible sales locations and organically certified producers. The majority of the attributes of organic rice are perceived as good by consumers, but for the attributes of the taste of rice and the packaging of rice, it is necessary to pay more attention because they are not in line with consumer expectations, so they are perceived as unfavorable